Analysis of students’ difficulties in solving probability questions: The case of advanced certificate of secondary education examination in Tanzania - Fadhili Mustafa Mrope; Emmanuel Deogratias (Universitas Sarjanawiyata Tamansiswa, 2024)
This study investigates students' performance in solving probability-related questions in the Advanced Certificate of Secondary Education Examination (ACSEE) in Tanzania. The purpose is to identify the challenges students face when tackling these problems and provide insights for improving their performance. Using analysis of exam responses, the study reveals that many students struggle with probability questions, particularly those involving probability distributions like Binomial and Poisson. The difficulties arise from conceptual misunderstandings, the complexity of probability tasks, and the inappropriate use of generalized problem-solving techniques. To address these issues, we recommend conducting protocol analysis to understand students' cognitive processes when solving probability problems. This approach could guide teachers in developing instructional strategies that enhance students' comprehension and application of probability concepts. The findings contribute to shaping educational policies and teaching practices that can improve mathematical literacy and performance in probability tasks.